(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The essential characteristics of the accounting provision of charity are highlighted. The main provisions of normative legal acts regarding the accounting support of charitable activities have been identified. Attention is focused on the regulatory and legal provision of the process of accounting and taxation of charitable assistance. Subjects and objects of charitable activity have been singled out in order to increase the efficiency of accounting. The main types and forms and the procedure for carrying out charitable activities for the Armed Forces of Ukraine are highlighted. In order to understand the subject to whom the charitable aid is transferred, the main components of the armed forces of Ukraine are structured. The main stages of organization and reflection in the accounting of the process of providing charitable assistance to the Armed Forces of Ukraine, which can be used in the process of carrying out charitable activities, both as a business entity and as a charitable organization, have been systematized. The sequence of the process of documenting the provision of charitable assistance and the main requisites and structural elements of such documents are given. Attention is focused on the peculiarities of calculating the tax liability from the value added tax on goods, works, and services donated to charity. The purpose of the scientific work is to develop and reveal theoretical provisions and substantiation of practical recommendations regarding the accounting provision of charity of economic entities. The following methods are used in this work: systematic approach, methods of comparison and analysis, classical statistical methods, methods of analysis and synthesis. Of practical importance are methodological recommendations regarding the accounting display of the process of providing charitable assistance during the war. An analysis of the development trends of charitable activities in Ukraine during the period of the full-scale invasion was carried out.